KAJIAN SEBARAN RADIOAKTIF GAMMA DALAM LINGKUNGAN AIRTANAH DI SISI SELATAN GUNUNGAPI MERAPI, DESA WUKIRSARI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN - , ANDREAS RONALDO PRATAMA LAKAFIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted in the village of Wukirsari Cangkringan sub- district of Sleman Regency. Nature radioactive is a radioactive which come from radiation on earth. The largest contributor of natural radionuclides against the magnitude of gamma exposure to human is Uranium daughter U-238 (Uranium-238). That radionuclides is very dangerous to human if it pollutes into groundwaters which will be used by human. This research aims to assess the distribution of gamma radioactive because of Merapi Volcano eruption on 2010 in free groundwaters at study area and to formulate environmental management strategies to handle the problem of groundwaters contamination potency by radioactive. This research was used survey method. Systematic method based on grid to determine sample point and groundwaters flow pattern. To obtain the data of groundwaters quality use purposive method which consider that sample point must be on one track at groundwaters flow that showed in flownet. The data obtained is activity data of radioactive and effective dose. The second objective is achieved by qualitative descriptive method which use the data of effective dose distribute as a alternative reference to formulate environmental management strategies. This result showed that gamma radioactive activity from U-238 on groundwaters at study area is still safe because it is still below the quality standards that based on the decision by the Head of the Nuclear Energy Regulatory Agency number: 02/Ka-BAPETEN/V-99 about standard level of radioactivity in the environment that is 1x103 Bq/litre in terms of U-238 activity in water. From the test results it was found that range of U-238 activity that is 0,123Â±0,04 Bq/litre until 0,283Â±0,011 Bq/litre. For the effective dose was found that effective dose distribution in the study area is still very low and safe that is 4,00 Î¼Sv/year until 8,14 Î¼Sv/year. The effective dose in the study area is still far below the WHO threshold specified that is 0,1 mSv/year for the magnitude of the effective dose in drinking water. Thus the effective dose in the study area is still safe and do not impact stochastic and non-stochastic effects (deterministic). Environmental management strategies conducted through preventive strategies which includes requirements management, engineering, radiation protection and safety stipulated in Government Regulation Number 33 of 2007 about ionizing radiation safety and security of radioactive sources, and Act number 32 / 2009 on environmental protection and management.